Inside the books : readers and libraries around the world - Buzzeo, Toni (Upstart Books, 2012)
"I love to look inside the books. They beckon me from wooden shelves that guard the stories hidden there ... All across the world, on every continent, there are libraries filled with books. Some libraries are big, and others small. Some libraries sit on land, others float on water, and still others nestle amidst ice and snow. Some libraries even bump along in wheel barrows!"--